COMPARATIVE ANALYSIS OF THE SOURCE AND TRANSLATED TEXT OF THE SELECTED POETRY BY FAIZ AHMAD FAIZ - Sumaira Aslam; Dr. Muhammad Arfan Lodhi (International Journal of Contemporary Issues in Social Sciences, 2024)
This study aims at finding equivalences and differences between the selected poems in Urdu by Faiz Ahmed Faiz and their translation in English by Mahmood Jamal. This research work identifies equivalences and differences at literary, pragmatic, and cultural levels between the source text in Urdu and the target text in English. The research design for the present study is exploratory. Out of Jamal’s translated fifty poems of Faiz Ahmed Faiz, the researcher has selected sixteen poems by applying a disproportionate random sampling technique. Keeping in view the objectives of the study, the selected poems and their translations have been analysed qualitatively through observation and content analysis by formulating a theoretical framework of analysis mostly based on the translation strategies suggested by Newmark. The study revealed that the translator has achieved varying degrees of equivalence at different levels. At the literary level, there exists a partial equivalence between the original Urdu poems and the translated English poems. At the pragmatic level, the translator has achieved a proximal degree of equivalence whereas the comparison at the cultural level reveals that there is a partial level of equivalence between the source text and the target text. Differences in translation do exist at all three levels. On literary and cultural levels, these differences are quite noticeable while at the pragmatic level, these differences are minor. The study concludes with recommendation of the inevitable need of translating the Urdu literature in foreign languages and the vice versa. In doing so, literary and cultural assimilation and propagation will not only enhance the readership but it will strengthen the geographical esprit de corps and cultural camaraderie.